Children’s digital playgrounds as data assemblages: Problematics of privacy, personalization, and promotional culture - Karen Louise Smith; Leslie Regan Shade (Big Data & Society, 2018)
Children’s digital playgrounds have evolved from commercialized digital spaces such as websites and games to include an array of convergent digital media consisting of social media platforms, mobile apps, and the internet of toys. In these digital spaces, children’s data is shared with companies for analytics, personalization, and advertising. This article describes children’s digital playgrounds as a data assemblage involving commercial surveillance of children, ages 3–12. The privacy sweep is used as a method to follow the personal information traces that can be expected to be disclosed through typical use of two children’s digital playgrounds: the YouTube Kids app and Fisher-Price Smart Toy plush animal and companion app. To trace the data flows, privacy policies and other publicly available documents were analyzed using political economy and privacy informed indicators. This article concludes by reflecting upon the dataveillance and commercialization practices that trouble the privacy rights of the child and parent when data assemblages in children’s digital playgrounds are surveillant.